(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
The research is based on the difficulties deaf people face in constructing texts. Its objective is to develop a methodology applicable to the Cuban Bilingual Model, based on the Cognitive Communicative and Sociocultural Approach to text construction in deaf people. The proposal is innovative and practical. It responds to the characteristics, needs, and potential of these individuals. A system of dimensions, indicators, and evaluation criteria is designed for diagnosis and intervention in working with text construction in deaf people. The necessary levels of assistance are established in the stages of orientation, execution, and control as recursive processes, and methodological guidelines are offered to teachers for its application.